Leap year [videorecording (DVD)] - Adams, Amy; Scott, Adam, 1973-; Goode, Matthew, 1978-; Lithgow, John, 1945- (Universal Studios Home Entertainment, 2009)
When Anna's four-year anniversary to her boyfriend passes without an engagement ring, she decides to take matters into her own hands. Inspired by an Irish tradition that allows women to propose to men on Leap Day, Anna follows Jeremy to Dublin to propose to him. But after landing on the wrong side of Ireland, she must enlist the help of Declan, a handsome and carefree local man, to get her across the country. Along the way, they discover that the road to love can take you to very unexpected places.